(untitled) (Research, Society and Development, 2022)
Mostly used in the therapy of individuals with malignant neoplasms or bone diseases, the group of bisphosphonates, whose mechanism is related to anti-osteoclastic properties, promotes changes in the bone remodeling capacity, generating the occurrence of a challenging management situation: osteonecrosis of the jaws. The present study aims to expose an alternative minimally traumatic management of tooth extraction, in order to avoid osteonecrosis of the jaws associated with the use of this class of drugs. This is a literature review carried out through the selection of articles available in PubMed, LILACS and Google Scholar databases, published between 2008 and 2021 in English and Portuguese. The literature points out that the occurrence of osteonecrosis of the jaws is related to the route of administration, treatment time and the dosage of bisphosphonate, with the intravenous route being the most associated with this condition due to its rapid absorption by the bone structure, which is a route widely used in patients undergoing chemotherapy, highlighting tooth extraction procedures as the main trigger of this condition. Based on the fact that this situation occurs mainly due to bone manipulation in oral surgery procedures, the importance of conservative management is emphasized so that osteonecrosis of the jaws is avoided, with tooth exfoliation with orthodontic elastics being a viable option with satisfactory results described by the literature.